Tertullian, first theologian of the West - Osborn, Eric (Cambridge University Press, 1996)
Tertullian was the first western Christian to write theology, defending Christians against the hostility of the Roman state, as well as arguing against Marcion, Praxeas and theosophical fantasy. A complex thinker, Tertullian has, in the modern era, been rejected by both liberal Christianity and its secular critics. But his ideas have become more accessible in our century, which has seen the destruction of Enlightenment beliefs that reason should lead to a quasi-mathematical system. The work of Gödel, Wittgenstein, Rorty and so many others has opened up the way for an understanding of Tertullian's passion for opposites, contingency and rational argument. For a long time misquoted and misused, Tertullian now calls for sustained analysis and interpretation. This book offers a major reappraisal of his theology and its influence on the shape of the western Christian tradition.